Determinants of the Utilization of Integrated Primary Care Services (ILP) Posyandu Among Older Adults in East Pekalongan District in 2026 - Sabrina Amna Fazaira; Ardiana Priharwanti; Dewi Nugraheni Restu Mastuti (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Integrated Primary Care Services (ILP) Posyandu is a community-based health program designed to improve the health status of older adults through integrated, comprehensive, and continuous healthcare services. However, the utilization of ILP Posyandu among older adults in East Pekalongan District remains suboptimal due to various predisposing, enabling, and reinforcing factors. This study aimed to analyze the determinants of ILP Posyandu utilization among older adults in East Pekalongan District in 2026. A quantitative analytical study with a cross-sectional design was conducted involving 99 older adults selected through purposive sampling with proportional distribution across urban villages. Data were collected using a validated and reliable structured questionnaire and analyzed using the Chi-square test and binary logistic regression. The results showed that the availability of healthcare facilities (p = 0.000), access to healthcare service locations (p = 0.003), family support (p = 0.001), and community health volunteer (cadre) support (p = 0.000) were significantly associated with ILP Posyandu utilization. In contrast, healthcare resources (p = 0.466) were not significantly associated with utilization. Multivariate analysis identified the availability of healthcare facilities (p = 0.024; Exp(B) = 0.272) and community health volunteer (cadre) support (p = 0.012; Exp(B) = 0.225) as the most influential determinants. Strengthening healthcare facilities and community health volunteer support is recommended to improve ILP Posyandu utilization.